Warning! This Product Contains Nuttiness : A Fun Look at the Bizarre World in Which We Live - Venable, Sam (Book collections on Project MUSE., 2013)
As seen through the eyes of the author, the world is indeed bizarre and filled with nuttiness. The archives of the Knoxville News Sentinel offer ample evidence that the author is a bit of the former and has made a career out of drawing attention to the latter. For this book, he gathered and organized 139 of his newspaper columns to create a trove of wit and wisdom. In the spirit of "The Emperor's New Clothes," he points a finger at human nature, the environment, civil rights and wrongs, and an eclectic mix of other targets, drawing our attention to the foibles, failings, and just plain absurdities that surround us all.